Performance-based Subsides: An Alternative Subsidy Regime for Passenger Rail Transport - Fearnley, Nils; Bekken, Jon-Terje (Proceedings from the Annual Transport Conference at Aalborg University, 2003)
The Norwegian Ministry of Transport’s (MoT) 2002 White Paper on Public Transport paved the way for the introduction of performance-based contracts for rail passenger service obligations (PSO). The rationale was that such contracts provide a better allocation of risk and responsibilities between authorities and the operators, and will give further incentives for cost and market efficient solutions in passenger rail operations. We have used a simulation model for public transport in order to estimate socially optimal subsidies, which encourage Norwegian State Railways (NSB) to increase patronage and to take external costs and benefits into account. By optimal subsidy regime we mean that the arrangement combines the social surplus maximising objectives of the MoT with the NSB's commercial goals, such that net social surplus (NSS) is maximised compared to the present situation. Within the model NSS comprises: (1) change in NSB’s profit (producer surplus); (2) change in passengers benefit (consumer surplus); (3) changes in environmental and congestion costs; and (4) resource cost of public funds. Through a series of model iterations we have designed a combination of subsidies per passenger, per train kilometre and for seat capacity. With these incentives, NSB will, on a commercial basis, strive towards service levels that resemble the social surplus maximising levels of service. The subsidies internalise the benefits to existing and new passengers and the effect on road congestion of rail service improvements into NSB’s decision criteria. They also reflect the fact that rail fares are regulated. The performance-based subsidies will bring about a welfare gain in the region of NOK 8 million (€1 equals about NOK 8). The subsidies received under this regime together with the passenger revenue, may exceed the costs of the operator. To cope with this, we recommend that a fee is charged for the right to operate under this contractual regime. There is a risk that the incentives will motivate the operators to focus their efforts entirely on train kilometre, seat capacity and passenger numbers to the degree that they overlook other important aspects of service quality, like punctuality, cleanliness, information etc. As a safety net, we recommend a set of additional conditions and bonus/malus arrangements. Most important are (1) bonus/malus for train cancellations and delays, based on the principles of internalising passengers’ benefits or costs into NSB’s decision criteria; and (2) the threat of tendering if quality measurements and performance levels fall below certain levels.